Social criteria in the drama of MoliÌ€ère - Brooks, Beverley Anne (Rhodes University, Faculty of Humanities, School of Languages, 1974)
It is by no means an easy task to analyse and interpret the work of a dramatist such as Molière, for an interval of three hundred years inevitably blurs our perspective of the man and his intentions. We find ourselves unconsciously reading more into his lines than he possibly meant us to. We are tempted to attach significance to certain words and disregard others, in an arbitrary fashion. We try to reconstruct Molière's attitude towards his contemporaries and theirs to him, from evidence that is often flimsy and seldom reliable. Molière's very identity has been questioned to the extent that the authorship of his plays has been variously attributed to such different personalities as Louis XIV and the great Corneilleo. To these problems is added a further complication when one embarks upon a thesis dealing with the picture of society as it emerges from Molière's plays. Not only are we confronted with the difficulty of interpretation already mentioned, but also with the vastly different way in which pre-enlightenment man regarded social and political institutions. We of the twentieth century tend to take for granted the notions of liberty, fraternity, and equality. Had anyone formulated such ideas in the seventeenth century, it is doubtful whether they would have been accepted, since they contradict the very concept upon which society was based in the age of Louis XIV. This concept, broadly speaking, is that of a strict hierarchy in which everyone has his own appointed place. Obviously the notion of a hierarchy pre-supposes the inferiority of some and the superiority of others in the social structure of the day; and post-enlightenment thinking does not readily accept that some men should be privileged and others regarded as belonging naturally to the lower orders. Intro., p. 1-2.
Keywords: Molière, 1622-1673 -- Criticism and interpretation